Freelancer’s E-Marketplace Information System Using Profile Matching Method - Riscal Arifin; Benny Daniawan; Dellih Wijaya (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2019)
Now development of information technology and internet is very high and increasingly widespread. With the technology which is connected without limits time and place. The development of online transactions is very much in demand compared to conventional transactions, without a medium to make the right transactions, it will hamper the efficiency and effectivenes, so that transaction activities between sellers and buyers become inhibited. Therefore we need a solution to solve these problems, the progress of e-commerce in Indonesia is needed for the community. Developing technology can be implemented into the business field. So an e-marketplace application is needed to be built and designed as a web to transact between sellers and buyers. This website is developed using the profile-matching method and with the design of RAD (Rapid Application Development) which is an object-oriented approach to the system with the main goal of shortening the application processing time and process so that as soon as possible empowering the software system precisely and quickly which consists of the requirements planning, design system, instruction and implementation. The e-marketplace information system can increase freelancer revenue and the level of customer convenience in finding workers according to what is needed and can make the transaction process efficient and effective. As a result, it helps to provide decision criteria for the client selection.